Health hazards of child labor in the leather products and surgical instrument manufacturing industries of Sialkot, Pakistan. (July 2017) - Junaid, Muhammad; Malik, Riffat Naseem; Pei, De-Sheng
Abstract: Child labor is a major challenge in the developing countries and comprehensive health hazard identification studies on this issue are still lacking. Therefore, the current study is an effort to highlight the health concerns of child labor exposed in the key small scale industries of Sialkot, Pakistan. Our findings revealed jolting levels of heavy metals in the urine, blood, serum, saliva, and hair samples collected from the exposed children. For example, in the urine samples, Cd, Cr, Ni, and Pb were measured at the respective concentrations of 39.17, 62.02, 11.94 and 10.53 μg/L in the surgical industries, and 2.10, 4.41, 1.04 and 5.35 μg/L in the leather industries. In addition, source apportionment revealed polishing, cutting, and welding sections in the surgical industries and surface coating, crusting, and stitching sections in the leather industries were the highest contributors of heavy metals in the bio-matrices of the exposed children, implying the dusty, unhygienic, and unhealthy indoor working conditions. Further, among all the bio-matrices, the hair samples expressed the highest bioaccumulation factor for heavy metals. In accordance with the heavy metal levels reported in the exposed children, higher oxidative stress was found in the children working in the surgical industries than those from the leather industries. Moreover, among heavy metals' exposure pathways, inhalation of industrial dust was identified as the primary route of exposure followed by the ingestion and dermal contact. Consequently, chemical daily intake (CDI), carcinogenic and non-carcinogenic hazard quotients (HQs) of heavy metals were also reported higher in the exposed children and were also alarmingly higher than the corresponding US EPA threshold limits. Taken all together, children were facing serious health implications in these industries and need immediate protective measures to remediate the current situation. Graphical abstract: Highlights: Children occupational exposure assessment via simultaneous biomonitoring of eight heavy metals in six biomatrices. Health risks estimation of indoor industrial dust through different exposure pathways. Heavy metals' industrial sources and associated oxidative stress to the child labor. Cr, Ni, Cd, and Pb were observed as metals inducing higher health impacts. Children were prone to heavy metals contamination in the surgical industries compared to the leather industries. Abstract : A comparative study highlighted the occupational health implications of heavy metals in children working in the key industrial sectors of Sialkot, Pakistan.